2023
DOI: 10.1097/sap.0000000000003606
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Representation of Invited Speakers From The Aesthetic Society Annual Meetings Over a 5-Year Period

Abstract: Background Increased representation from both women and non-White ethnicities remains a topic of discussion in plastic surgery. Speakers at academic conferences are a form of visual representation of diversity within the field. This study determined the current demographic landscape of aesthetic plastic surgery and evaluated whether underrepresented populations receive equal opportunities to be invited speakers at The Aesthetic Society meetings. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Jacobson et al 123 reported that the proportion of female speakers at hand surgery meetings increased from 4% to 19% between 2010 and 2020. Similarly, Finkelstein et al 120 found that the proportion of female invited speakers increased over 5 years to 20%. In 2023, Maisner et al 117 reported that female medical students presented 53.5% of the abstracts at the 2019 and 2020 meetings of the American Society of Plastic Surgeons, American Association of Plastic Surgeons, and the Plastic Surgery Research Council.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Jacobson et al 123 reported that the proportion of female speakers at hand surgery meetings increased from 4% to 19% between 2010 and 2020. Similarly, Finkelstein et al 120 found that the proportion of female invited speakers increased over 5 years to 20%. In 2023, Maisner et al 117 reported that female medical students presented 53.5% of the abstracts at the 2019 and 2020 meetings of the American Society of Plastic Surgeons, American Association of Plastic Surgeons, and the Plastic Surgery Research Council.…”
Section: Resultsmentioning
confidence: 86%
“…Ha et al 112 reported that underrepresented surgeons comprise 8.3% of practicing plastic surgeons but 4.7% of speakers. By contrast, Finkelstein et al 120 reported that 23% of the speakers at meetings of the American Society for Aesthetic Plastic Surgery, from 2017 to 2021, were non-White. Chawla et al 60 reported that citations and h-indices of White and non-White academic plastic surgeons were comparable.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations